2003
DOI: 10.1248/cpb.51.215
|View full text |Cite
|
Sign up to set email alerts
|

Bacopasides III-V: Three New Triterpenoid Glycosides from Bacopa monniera.

Abstract: In continuation of our studies 1,2) on the bioactive glycosidic fraction of Bacopa monniera, a herb having confirmed nervine tonic activity, [3][4][5] we undertook a reinvestigation of the n-butanol soluble fraction of the methanol extract of the plant. Earlier workers reported six saponins, viz. bacopasaponins A-F from the same fraction. [6][7][8] During the present investigation, we have extensively used HPLC for isolation of the minor constituents and finally have been able to isolate three new triterpenoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 8 publications
0
46
0
Order By: Relevance
“…Identity and purity (Ͼ95%) of the isolated compounds were confirmed by chromatographic (TLC, HPLC) and spectral (IR, Mass and NMR) data. [17][18][19][20][21][22][23][24] Bacopa monnieri plant materials, extracts analyzed in this study were supplied by M/s Laila Impex, Vijayawada, India and commercial formulations containing Bacopa monnieri were procured from the local market and Australia. Methanol and acetonitrile (HPLC grade), sodium sulphate and sulphuric acid (analytical grade) were purchased from Qualigens (Mumbai, India).…”
Section: Methodsmentioning
confidence: 99%
“…Identity and purity (Ͼ95%) of the isolated compounds were confirmed by chromatographic (TLC, HPLC) and spectral (IR, Mass and NMR) data. [17][18][19][20][21][22][23][24] Bacopa monnieri plant materials, extracts analyzed in this study were supplied by M/s Laila Impex, Vijayawada, India and commercial formulations containing Bacopa monnieri were procured from the local market and Australia. Methanol and acetonitrile (HPLC grade), sodium sulphate and sulphuric acid (analytical grade) were purchased from Qualigens (Mumbai, India).…”
Section: Methodsmentioning
confidence: 99%
“…28 Chemical characterizations of the plant have been carried out by many investigators. [29][30][31][32][33][34][35][36][37][38][39][40] There are no data currently available on the pharmacokinetics of Bacopa or its saponins. Phase I clinical studies confirmed the safety of bacosides in healthy male volunteers at both single and chronic dosing administered over a period of 4 weeks 7 and 6 weeks with a dose of up to 450 mg of dried water extract.…”
mentioning
confidence: 99%
“…The major chemical constituents isolated and characterized from B. monnieri are dammaranes of triterpenoid saponins with pseudojujubogenin glycosides or jujubogenin glycosides (Chakravarty et al, 2001(Chakravarty et al, , 2003Hou et al, 2002;Kamonwannasit et al, 2008).…”
Section: Phytochemical Substancesmentioning
confidence: 99%
“…Neuroprotective activity: The active constituents responsible for B. monnieri's cognitive effects are bacosides A and B, moreover, triterpenoid saponins are responsible to enhance nerve impulse transmission (Mahato et al, 2000;Hou et al, 2002;Chakravarty et al, 2001;2003). The bacosides also aid in repair of damaged neurons by enhancing kinase activity, neuronal synthesis, restoration of synaptic activity, and nerve impulse transmission (Singh and Dhawan, 1997).…”
Section: Phytochemical Substancesmentioning
confidence: 99%